Rationale for logistics operator infrastructure parameters - Gladkovska, Valentyna (Technology audit and production reserves, 2017)
The object of research is the infrastructure of the logistics operator. One of the most problematic places in the design of a logistics infrastructure is that the freight forwarding company must take into account the many interrelated factors that can affect it. As a result of lack of detail, the interval T considered in the research is divided into stages. This will determine the phased formation of the infrastructure of the logistics operator, as well as the gradual increase in the intensity of servicing material flows, and phased financing of a logistics infrastructure creation. The developed economic-mathematical model allows to obtain a solution to the problem of designing the infrastructure of a logistics operator. The model belongs to the class of non-linear programming problems and can be solved with the help of standard software. Parameters of the model management are the capacity and level of equipment of warehouses in the regions, the composition of the fleet, the number and type of trucks. This will allow the transport and forwarding company to determine the prospects for its presence in the regional markets in question as a logistics operator and enter the new markets in the development process and also become part of the logistics infrastructure of the regions. In the future, this model will contribute to the optimal organization of cargo transportation and the provision of services, which will lead to increased competitiveness of the freight forwarding company by attracting additional cargo volumes.